The complete chloroplast genome sequence and phylogenetic analysis of the medicinal plant Rubus chingii Hu - Qirui Wang; Shuisheng Yu; Chenshu Gao; Yuqing Ge; Rubin Cheng (Mitochondrial DNA. Part B. Resources, 2020)
Rubus chingii Hu is an important traditional Chinese medicine with a beneficial effect on the kidney. In this study, we report the complete chloroplast genome sequence of R. chingii. The assembled chloroplast genome was 155843 bp in length, containing two inverted repeated (IR) regions of 25372 bp each, a large single copy (LSC) region of 86456 bp and a small single copy (SSC) region of 18643 bp. The genome contained 130 genes, including 86 protein genes, eight rRNA genes, and 36 tRNA genes. The overall GC content of complete chloroplast genome was 37.1%. Phylogenetic analysis demonstrated that R. chingii clustered together with the monophyletic group of R. crataegifolius and R. takesimensis, suggesting a close relationship among the three species from Tribe Rubeae.